Attractiveness Differentially Affects Direct Versus Indirect Face Evaluations in Two Cultures - Cassidy, Brittany S; Saribay, S Adil; Yüksel, Hüseyin; Kleisner, Karel (Evolutionary psychology, 2023)
Although decades of research have identified facial features relating to people's evaluations of faces, specific features have largely been examined in isolation from each other. Recent work shows that considering the relative importance of these features in face evaluations is important to test theoretical assumptions of impression formation. Here, we examined how two facial features of evolutionary interest, facial attractiveness and facial-width-to-height ratio (FWHR), relate to evaluations of faces across two cultures. Because face evaluations are typically directly measured via self-reports, we also examined whether these features exert differential effects on both direct and indirect face evaluations. Evaluations of standardized photos naturally varying in facial attractiveness and FWHR were collected using the Affect Misattribution Procedure in the United States and Turkey. When their relative contributions were considered in the same model, facial attractiveness, but not FWHR, related to face evaluations across cultures. This positive attractiveness effect was stronger for direct versus indirect evaluations across cultures. These findings highlight the importance of considering the relative contributions of facial features to evaluations across cultures and suggest a culturally invariant role of attractiveness when intentionally evaluating faces.
Keywords: obličej; Biological Evolution; postoj; krása; cross-cultural effects; facial width-to-height ratio; Beauty; Humans; Face; Attitude; lidé; affect misattribution procedure; face perception; biologická evoluce; facial attractiveness